2017
DOI: 10.1001/jamapsychiatry.2016.3199
|View full text |Cite
|
Sign up to set email alerts
|

Proton Chemical Shift Imaging of the Brain in Pediatric and Adult Developmental Stuttering

Abstract: This spectroscopy study of stuttering demonstrates brainwide neurometabolite alterations, including several regions implicated by other neuroimaging modalities. Prior ascription of a role in stuttering to inferior frontal and superior temporal gyri, caudate, and other structures is affirmed. Consistent with prior functional magnetic resonance imaging findings, these results further intimate neurometabolic aberrations in stuttering in brain circuits subserving self-regulation of speech production, attention, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 58 publications
1
7
0
Order By: Relevance
“…These findings are consistent with previous anatomical studies reporting reduced gray matter volumes and reduced fractional anisotropy in the left or bilateral IFG [ 17 19 ], as well as with previous fMRI studies reporting lower intrinsic functional connectivity in the left IFG [ 39 ] and deficient left hemisphere connectivity between inferior frontal and premotor cortices under auditory and visual stimulation [ 63 ]. Our finding of reduced intrinsic functional connectivity of the IFG is also consistent with our prior findings of reduced perfusion and reduced spectroscopic indices of neural density in Broca’s region in the same sample of participants as included in the present study [ 5 , 10 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These findings are consistent with previous anatomical studies reporting reduced gray matter volumes and reduced fractional anisotropy in the left or bilateral IFG [ 17 19 ], as well as with previous fMRI studies reporting lower intrinsic functional connectivity in the left IFG [ 39 ] and deficient left hemisphere connectivity between inferior frontal and premotor cortices under auditory and visual stimulation [ 63 ]. Our finding of reduced intrinsic functional connectivity of the IFG is also consistent with our prior findings of reduced perfusion and reduced spectroscopic indices of neural density in Broca’s region in the same sample of participants as included in the present study [ 5 , 10 ].…”
Section: Discussionsupporting
confidence: 93%
“…Other DTI studies have also shown that adults who stutter have reduced fractional anisotropy (FA) in the left sensorimotor cortex [ 21 22 ]. Our recent spectroscopy study in the same participants of the present study reported reduced levels of N-acetyl aspartate (NAA), an index of neural density, in inferior and superior frontal cortices (including Broca’s region) and caudate nucleus, and increased NAA in the posterior cingulate, lateral parietal, and parahippocampal cortices, as well as the hippocampus and amygdala [ 5 ].…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…The pathophysiology of stuttering is still unclear. There is, however, increasing evidence of subtle structural and functional differences in the brains of adults and children who stutter relative to their fluent peers [Beal et al, 2013;Chang et al, 2015Chang et al, , 2017Chang and Zhu, 2013;Connally et al, 2014;Cykowski et al, 2010;Desai et al, 2017;O'Neill et al, 2017;Watkins et al, 2008]. One line of research investigated the property of white matter microstructure by measuring fractional anisotropy (FA), which reflects white matter coherence or integrity, through diffusion tensor imaging (DTI).…”
Section: Introductionmentioning
confidence: 99%
“…The spatial normalization faithfully preserved the MRS data into the high-resolution anatomical MRI space, as our previously published study demonstrated that the region-of-interest based findings matched the voxelwise findings. [38] We normalized the low-resolution MRS data into the high-resolution anatomical space for the following two reasons. (1) We wanted to generate within-individual metabolites maps that were adjusted for the partial volume of various brain tissues as an MRS voxel at a 1000 mm 3 resolution contains varying amounts of gray matter (GM), white matter (WM), and cerebrospinal fluid (CSF).…”
Section: Methodsmentioning
confidence: 99%